Dinamika Madrasah : Potret Lima Tahun Menjadi Sekolah Umum - Amien Haedari (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
This paper attempts to portrait the journey of madrasah (religious school) during the last five years, i.e. since the enactment of Law of RI number 20 of 2003 regarding the National educational system which poditions a madrasah as general school. This reposition is actually positive for the sustainability as well as improving the quality of madrasah. However, it should be noted that more than 90% of madrasah are managed by public. this means that madrasah still has to be developed according to the public requierements, not that government. Thus, to create a policy on madrasah, it obviously is necessary to accommodate various public interests. Exactly, it is needed a harmonious and dynamics convergency between the government and the people.